Characterizing the distribution and rates of microbial sulfate reduction at Middle Valley hydrothermal vents - Frank, Kiana L; Rogers, Daniel R; Olins, Heather C; Vidoudez, Charles; Girguis, Peter R (ISME JOURNAL, 2013)
Few studies have directly measured sulfate reduction at hydrothermal vents, and relatively little is known about how environmental or ecological factors influence rates of sulfate reduction in vent environments. A better understanding of microbially mediated sulfate reduction in hydrothermal vent ecosystems may be achieved by integrating ecological and geochemical data with metabolic rate measurements. Here we present rates of microbially mediated sulfate reduction from three distinct hydrothermal vents in the Middle Valley vent field along the Juan de Fuca Ridge, as well as assessments of bacterial and archaeal diversity, estimates of total biomass and the abundance of functional genes related to sulfate reduction, and in situ geochemistry. Maximum rates of sulfate reduction occurred at 90 degrees C in all three deposits. Pyrosequencing and functional gene abundance data revealed differences in both biomass and community composition among sites, including differences in the abundance of known sulfate-reducing bacteria. The abundance of sequences for Thermodesulfovibro-like organisms and higher sulfate reduction rates at elevated temperatures suggests that Thermodesulfovibro-like organisms may have a role in sulfate reduction in warmer environments. The rates of sulfate reduction presented here suggest that-within anaerobic niches of hydrothermal deposits-heterotrophic sulfate reduction may be quite common and might contribute substantially to secondary productivity, underscoring the potential role of this process in both sulfur and carbon cycling at vents.
Keywords: HOV Alvin (Human Occupied Vehicle)